2007
DOI: 10.1038/emm.2007.66
|View full text |Cite
|
Sign up to set email alerts
|

Bee venom stimulates human melanocyte proliferation, melanogenesis, dendricity and migration

Abstract: Pigmentation may result from melanocyte proliferation, melanogenesis, migration or increases in dendricity. Recently, it has been reported that secreted phospholipase A 2 (sPLA 2 ) known as a component of bee venom (BV), stimulates melanocyte dendricity and pigmentation. BV has been used clinically to control rheumatoid arthritis and to ameliorate pain via its anti-inflammatory and antinociceptive properties. Moreover, after treatment with BV, pigmentation around the injection sites was occasionally observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
2
27
1
1
Order By: Relevance
“…In a recent study, we showed that bee venom increases melanogenesis in human melanocytes (Jeon et al, 2007). Moreover, it has been shown that extracts from some herbs, including glycyrrhizin (Jung et al, 2001), Kava rhizome extract (Matsuda et al, 2006) or quercetin (Nagata et al, 2004), increase melanogenesis in B16 melanoma cells, thereby indicating that natural resources should be extensively screened for the development of gray hair prevention agents or therapeutic drugs to induce repigmentation in the skin of vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that bee venom increases melanogenesis in human melanocytes (Jeon et al, 2007). Moreover, it has been shown that extracts from some herbs, including glycyrrhizin (Jung et al, 2001), Kava rhizome extract (Matsuda et al, 2006) or quercetin (Nagata et al, 2004), increase melanogenesis in B16 melanoma cells, thereby indicating that natural resources should be extensively screened for the development of gray hair prevention agents or therapeutic drugs to induce repigmentation in the skin of vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we found that melanogenesis of B16F10 cells by the MA extract (20 µg/ml) was rapid and that the pellet color of cells was enhanced within 4 h after treatment. To compare the melanogenic effect of MA with other agents, we used the well-known melanogenic inducer forskolin at a concentration (20 µM) that is higher than the concentrations (5 or 10 µM) usually used in other groups (34,35). After incubation with the MA extract (20 µg/ml) for 8 h, the pellet color was darker than that incubated with forskolin (20 µM) for 48 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bee venom is regarded as ineffective and dangerous because it induces systemic inflammation. However, purified honey bee venom (apitoxin) may be effective in vitiligo (Jeon et al, 2007). Rhododendron schlippenbachii and Lespedeza bicolor show significant improvement in vitiligo lesions when applied topically or combined with phototherapy.…”
Section: Folk Remedies In Koreamentioning
confidence: 99%